Source of life revitalisation rites and bon shamans in Bhutan and the eastern Himalayas - Huber, Toni, 1956- (Austrian Academy of Sciences Press, 2020)
In this work three new inquiries into little-known highland populations of the extended Eastern Himalayas are presented. The central concern is ethnographic documentation of peoples? proactive quest for life, in terms of fertility, virility, procreation and revitalisation by way of practicing their ritual cultures. The work also provides fresh perspectives for understanding ?bon?-identified cultural phenomena in Himalayan and Tibetan societies. The final inquiry explores new hypotheses about the ethnolinguistic identities and prehistory of speakers within the Tibeto-Burman language family.
Keywords: Buddhism -- Bhutan.; Buddhism -- Himalaya Mountains.; Fasts and feasts -- Buddhism.; Bouddhisme -- Bhoutan.; Bouddhisme -- Himālaya.; Fêtes religieuses -- Bouddhisme.; Buddhism; Fasts and feasts -- Buddhism; Bhutan; Himalaya Mountains